Complementary Therapy Training for Teenager in Reducing the Prevalence Rate of Stunting: An Experimental Study - Martha Debora, Korompis; Losu, Frederika Nancy; Tombokan, Sandra Gerce Jelly (STIKes Patria Husada Blitar, 2025)
It is not yet known precisely which targets and forms of health education can be used in handling stunting both on a national and global scale. This gap requires study to find an effective and efficient solution. This research aimed to examine the target and whether complementary therapy methods, health education, are appropriate in preventing stunting. This research used quantitative methods with an experimental design. Carried out in Gogagoman Village, subdistrict of Kotamubagu Barat of Bolmong Raya, North Sulawesi. The population was 76 teenagers, and the sample was 50. The instrument used a questionnaire distributed online. The inclusion criteria was teenagers who lived in Bolmong Raya. The exclusion criteria was teenagers who lived outside Bolmong Raya. Primary data was from the questionnaires, pre and post-tests. The secondary data came from reputable journals. The training participants were divided into two groups, 25 people in the treatment group and 25 people in the control group. Data analysis used SPPS by conducting a paired t-test. The average knowledge value of 25 respondents in the control group after participating in the training increased by 16%. The treatment group was an increase of 7.3%. This complementary therapy training, play major role in preventing and overcoming stunting with a p-value (0.001 and 0.034) < 0.05, which means there is a significant difference between before and after training. It is recommended that complementary therapy and health education programs targeting teenagers in Bolmong Raya, North Sulawesi, be implemented as an effective strategy for preventing and addressing stunting.